Strategi Kepala Sekolah dalam Penerapan Budaya Religius di SMP Swasta Sinar Husni Helvetia - Marpaung, Jelita Ramadhani; Rifa'i, Muhammad (Universitas Negeri Malang, 2024)
Abstract: This research was conducted to gain an understanding of the theme of this research, namely the principal's strategy in implementing religious culture at Sinar Husni Helvetia Private Middle School, which consists of the principal's steps in his strategy, implementation of religious culture (customs), and inhibiting and supporting factors in advancing The principal's strategy in implementing religious culture at Sinar Husni Helvetia Middle School. Meanwhile, the research method used is a qualitative method which is descriptive and predominantly uses analysis. This research comes from several clear informants, the first is an informant from the school principal, the second is an informant from the deputy principal, the third is a religious teacher informant, and the fourth is an informant from students. The data collection methods used for this research were observation, interviews and documentation. The stages of the data collection or data reduction process, drawing conclusions and presenting data are the Miles & Huberman data analysis model. The results of this research show that; Firstly, the strategies used or used by the principal to implement religious culture at Sinar Husni Helvetia Private Middle School are cultural strategies (habituation), role model strategies (exemplary), and finally cooperation strategies (partnership). Second, the implementation of culture or religious habits in schools through the example method and habituation to good things that are often done by schools, namely habits or culture such as; in everyday application but which is often ignored by today's young people, namely the 3S of smiling, saying hello, saying hello. The next habit is to carry out the noon prayer every day in congregation and have a separate punishment for not carrying it out, as well as celebrating Islamic holidays, listening to religious sermons every week with different ustadz, reading prayers and reciting verses from the holy Koran. in the form of short surahs or surahs that students have memorized before starting class lessons. Third, the inhibiting and supporting factors for the implementation of this religious culture include; The supporting factors are the discipline of teachers and students, good infrastructure so that they can support the implementation of teaching and learning activities and preserve religious cultural habits, the unity of the school community and strong commitment, while the inhibiting factor is the reduced awareness of students or learners.Keywords: Implementation, Religious Culture, Strategy. Abstrak: Diadakannya penelitian ini untuk mengetahui pemahaman tentang tema penelitian ini yaitu strategi kepala sekolah dalam penerpana budaya religius di SMP Swasta Sinar Husni Helvetia, yang terdiri dari langkah-langkah kepala sekolah dalam strateginya, pelaksanaan budaya (kebiasaan) religius, dan faktor penghambat dan pendukungnya dalam memajukan strategi kepala sekolah dalam menerapkan budaya religius di SMP Sinar Husni Helvetia. Sedangkan metode penelitian yang digunakan ini adalah menggunakan metode kualitatif yang sifatnya deskriptif serta dominan menggunakan analisis. Penelitian ini bersumber dari beberapa informan yang sudah jelas, yang pertama informan dari kepala sekolah, kedua informan wakil kepala sekolah, ketiga informan guru agama, dan keempat informan dari peserta didik. Metode pengumpulan data untuk penelitian ini yang digunakan adalah observasi, wawancara dan dokumentasi. Tahapan proses pengumpulan data atau reduksi data, mengambil kesimpulan serta penyajian data adalah model analisis data Miles & Huberman. Hasil dari penelitian ini menunjukkan bahwa; pertama, strategi yang dipakai atau digunakan oleh kepala sekolah untuk menerapkan budaya religius di SMP Swasta Sinar Husni Helvetia ini adalah strategi kebudayaan (pembiasaan), strategi panutan (keteladanan), dan terakhir strategi jalinan kerja sama (kemitraan). Kedua, pelaksanaan budaya atau kebiasaan religius di sekolah melalui metode tauladan serta pembiasaan hal baik yang sering dilakukan oleh sekolah yaitu pembiasaan atau kebudayaan seperti; dalam penerapan yang dilakukan sehari-hari tapi sering diabaikan oleh anak muda zaman sekarang yaitu 3S senyum, sapa, salam. Pembiasaan selanjutnya yaitu melaksanakan salat zuhur setiap harinnya secara berjamaah dan memiliki hukuman tersendiri jika tidak melaksanakannya, serta melangsungkan perayaan hari-hari besar islam, mendengarkan tausiah agama disetiap minggunya dengan ustadz yang berbeda-beda, membaca doa dan melafazkan ayat suci Al-Qur’an berupa suirah-surah pendek atau surah yang sudah dihafal para peserta didik sebelum memulai pelajaran dikelas. Ketiga, untuk faktor penghambat dan pendukung agar terlaksananya budaya religius ini antara lain; faktor pendukungnya yaitu kedisplinan guru dan siswa, sarana prasarananya yang baik sehingga dapat mendukung terlaksananya kegiatan belajar mengajar serta melestarikan kebiasaan budaya religius, terjalinnya kebersamaan masyarakat sekolah serta komitmen yang kuat, sedangkan faktor penghambatnya adalah kurangnya kesadaran siswa atau peserta didik.Kata kunci: Penerapan, Budaya Religius, Strategi